2016
DOI: 10.3390/bios6040050
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Fabrication and Application of Screen-Printed Electrochemical (Bio)Sensors Based on Carbon Materials for Biomedical, Agri-Food and Environmental Analyses

Abstract: This review describes recent advances in the fabrication of electrochemical (bio)sensors based on screen-printing technology involving carbon materials and their application in biomedical, agri-food and environmental analyses. It will focus on the various strategies employed in the fabrication of screen-printed (bio)sensors, together with their performance characteristics; the application of these devices for the measurement of selected naturally occurring biomolecules, environmental pollutants and toxins will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 170 publications
1
56
0
Order By: Relevance
“…Initial cyclic voltammetric studies were performed to characterise the electrochemical behaviour of the cobalt phthalocyanine screen printed carbon electrodes (CoPC‐SPCEs) for the measurement of hydrogen peroxide. This particular electrocatalyst has been found to be effective for the electroxidation of hydrogen peroxide and has been used by our group and others in numerous studies . It was important to understand the electrochemical behaviour of hydrogen peroxide with this new electrode configuration, as it is the product of the reaction of numerous oxidase enzymes with their appropriate substrates.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…Initial cyclic voltammetric studies were performed to characterise the electrochemical behaviour of the cobalt phthalocyanine screen printed carbon electrodes (CoPC‐SPCEs) for the measurement of hydrogen peroxide. This particular electrocatalyst has been found to be effective for the electroxidation of hydrogen peroxide and has been used by our group and others in numerous studies . It was important to understand the electrochemical behaviour of hydrogen peroxide with this new electrode configuration, as it is the product of the reaction of numerous oxidase enzymes with their appropriate substrates.…”
Section: Figuresupporting
confidence: 89%
“…In the next part of the study we investigated the new design comprising of a working electrode containing the enzyme glucose oxidase. Chronoamperometric calibration studies were carried out at an applied potential of +450 mV (versus Ag/AgCl); this value was deduced from the CV responses (Figure ) and agrees well with our previous studies using a CoPC‐SPCE . In our previous research, we have found that the first part of our voltammetric response was due to the re‐oxidation of Co + to Co 2+ , which occurred at around +450 mV.…”
Section: Figurementioning
confidence: 95%
“…In recent years, many reports on screen‐printed carbon electrodes (SPCEs) technology have been used to develop various electrochemical sensors that detect target molecules in various sectors, such as biomedical environmental and agri‐food . SPCE is planar shape, thus can be used as droplet on sensor, using typically few microliters (μL) of the sample in miniaturized system.…”
Section: Introductionmentioning
confidence: 94%
“…Current challenges associated with electrochemical sensor miniaturization include the generation of low electrochemical currents, higher diffusion rates of the electroactive analytes, and high microelectrode surface area to solution volume ratios. These physical and chemical phenomena result in better electrochemical signal‐to‐noise ratios; however, the higher adsorption rate of molecules onto the microelectrode surface and the higher faradaic currents from both the analyte and the interfering molecules consequently decrease the selectivity of the sensor for the in situ analysis of biofluids . For this study, we electrodeposited micrometer‐thick film of chitosan–CNT onto a 50 µm disk microelectrode.…”
Section: Introductionmentioning
confidence: 99%